Država in suverenost v dobi globalizacije - Ahtik, Meta (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2011)
The concept of economic sovereignty has become increasingly important in the last decades. It is viewed as the ability of state to promote growth and development by using monetary, fiscal, trading and industrial policy while at the same time taking into consideration the exogenous factors (world market conditions, etc). By joining different types of regional economic integrations (REI) states give up some components of their economic sovereignty and transfer them to REI in order to promote economic development and growth. The aim of this article is to identify different parts of economic sovereignty which are lost or being limited by membership indifferent types of REI. Cases of European Union and euro area are being analysed in detail.
Keywords: economic sovereignty; European Union; Evropska unija; globalizacija; globalization; regional economic integrations; transfer of economic sovereignty to REI; integracija; države; EU and national economic sovereignty; suverenost; regionalno gospodarstvo; regionalne ekonomske integracije; ekonomska suverenost; prenos ekonomske suverenosti